Influence of seed layer thickness on properties of electrodeposited ZnO nanostructured films - Reyes Tolosa, M. D. (2019)
The quality and properties of electrodeposited nanostructured ZnO films are improved when they are deposited on a crystal lattice-matching substrate. To this end, a highly conductive indium tin oxide substrate is covered with an interlayer of ZnO using direct-current magnetron sputtering. In this manuscript, we describe the effect of this interlayer on the morphological and optical properties of several nanostructured ZnO films grown by different electrodeposition methods. The thickness of the ZnO interlayer was varied starting from ultrathin layers of 10 nm all the way up to 230 nm as determined by ellipsometry. The structural and optical properties of the nanostructured ZnO films deposited on top of these interlayers were characterized using field emission scanning electron microscopy (FESEM), atomic force microscopy and UV–visible spectroscopy. Optimum properties of the nanostructured ZnO films for application in thin-film optoelectronic devices are obtained when the ZnO interlayer has a thickness of approximately 45 nm. This is the case for all the electrodeposition methods used in this work.